National Prostate Cancer Screening Rates After the 2012 US Preventive Services Task Force Recommendation Discouraging Prostate-Specific Antigen-Based Screening - Drazer, Michael W; Huo, Dezheng; Eggener, Scott E (Journal of clinical oncology, 2015)
In 2012, the US Preventive Services Task Force (USPSTF) discouraged prostate-specific antigen (PSA) -based prostate cancer screening. Previous USPSTF recommendations did not appreciably alter prostate cancer screening. Therefore, we designed a trend analysis to determine the population-based impact of the 2012 recommendation. The nationally representative National Health Interview Survey was used to estimate the proportion of men age 40 years and older who saw a physician and were screened for prostate cancer in 2013. An externally validated 9-year mortality index was used to analyze screening rates based on remaining life expectancy. Screening rates from 2005, 2010, and 2013 were compared using logistic regression. PSA-based screening did not significantly change from 2010 to 2013 among 40- to 49-year-old men (from 12.5% to 11.2%; P = .4). Screening rates significantly declined in men age 50 to 59 years (from 33.2% to 24.8%; P < .01), age 60 to 74 years (from 51.2% to 43.6%; P < .01), and age 75 years or older (from 43.9% to 37.1%; P = .03). A large percentage of men were screened for prostate cancer despite a high risk (> 52%) of 9-year mortality, including approximately one third of men older than age 75 years. Approximately 1.4 million men age 65 years or older with a high risk (> 52%) of 9-year mortality were screened in 2013. Prostate cancer screening significantly declined among men older than age 50 years after the 2012 USPSTF guideline discouraging PSA-based screening. A significant proportion of men continue to be screened despite a high risk of 9-year mortality, including one third of men age 75 years and older.